98.9k views
3 votes
Prove that:- (1-sinA)(1+sinA)÷(1+cosA)(1-cosA)=cot^2A​

User Eoredson
by
6.2k points

1 Answer

1 vote

Answer:

see explanation

Explanation:

Using the trigonometric identity

sin²x + cos²x = 1 , then

sin²x = 1 - cos²x and cos²x = 1 - sin²x

Consider the left side


((1-sinA)(1 + sinA))/((1+cosA)(1-cosA)) ← expand numerator/denominator using FOIL

=
(1-sin^2A)/(1-cos^2A)

=
(1-(1-cos^2A))/(1-(1-sin^2A))

=
(1-1+cos^2A)/(1-1+sin^2A)

=
(cos^2A)/(sin^2A)

= cot²A = right side , thus proven

User Mark Maxey
by
6.6k points